Isolasi dan Identifikasi Bakteri Lipolitik Indigenous untuk Bioremediasi Tanah Limbah Pabrik Kelapa Sawit - Muhammad Nor; Noor Hujjatusnaini; Ridha Nirmalasari (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to isolate, identify, and test the potential of native lipolytic bacteria from LCPKS contaminated soil, as well as to determine the effect of supplementation of oil palm leaf midrib extract on its degradation activity. The research method uses an experimental design with isolation techniques and morphological characterization of bacteria, followed by a lipolytic test on Nutrient Agar Fat (NAL) medium and a bioremediation test using oil palm leaf midrib extract at concentrations of 0.1%, 0.5%, and 1%. The results showed that there were nine types of colonies with three dominant bacteria, namely Candida spp. (95 colonies), Streptomyces sp. (11 colonies), and Aspergillus spp. (4 colonies). The three bacteria were shown to be lipolytically active, as evidenced by the formation of a clear zone in the NAL medium. Supplementation with oil palm frond extract significantly increased colony growth, with the highest yield at a concentration of 1% (>360 colonies/15 mL). ANOVA analysis showed differences in degradation effectiveness between colonies, with Aspergillus spp. exhibiting higher activity than other colonies. These findings confirm that the use of indigenous lipolytic bacteria in combination with oil palm frond extract can be a sustainable bioremediation strategy to reduce oil and fat content in LCPKS.